Global Landscapes: Teaching Globalization through Responsive Mobile Map Design. Issue 3 (3rd July 2018) - Roth, Robert; Young, Stephen; Nestel, Chelsea; Sack, Carl; Davidson, Brian; Janicki, Julia; Knoppke-Wetzel, Vanessa; Ma, Fei; Mead, Rashauna; Rose, Caroline; Zhang, Guiming
Abstract : This article reports on the design and evaluation of Global Madison, a mobile map designed to support teaching and learning about globalization using Madison, Wisconsin, as a situated classroom. Our experience of place increasingly is mediated by mobile devices, opening new opportunities and challenges for research, industry, and education. Despite this rising popularity, few guidelines exist for creating and using mobile maps. Following tenets of user-centered design studies, we conducted two mixed-method evaluations of Global Madison to improve the tool and generate design insights that are potentially transferable to similar mobile mapping contexts: 244 students participated in an online survey after completing the tour and eighteen students were observed in the field. The evaluations generated new design considerations for mobile maps supporting situated learning, include: focus on critical issues that might leave students stranded, append location-based services with traditional mapping, enforce cognitive association between map and landscape, supply a consistent feed of information for new learners, encourage collaborative learning in the landscape, and promote student safety above all else.